PERAN MEDIASI MOTIVASI KERJA TERHADAP HUBUNGAN MODAL PSIKOLOGIS DAN KREATIVITAS INDIVIDU PADA KARYAWAN PERILAKU KERJA INOVATIF - Wahyuningsih, Siwi -; Suhana, Suhana (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to examine the influence of psychological capital, individual creativity on work motivation and its impact on innovative work behavior. The population of this research is civil servants in North Semarang District, totaling 115 people. The sample for this research was 115 employees. Thus, the sampling technique used was a saturated sampling technique, the entire population was sampled. The data analysis used is multiple linear regression analysis. The research results show that psychological capital has a significant influence on innovative work behavior. Meanwhile, individual creativity does not have a significant effect on innovative work behavior. Other research results show that employee psychological capital and creativity have a positive influence on work motivation. Work motivation influences innovative work behavior. The research results also show that work motivation acts as a mediating variable in the influence of psychological capital and individual creativity on innovative work behavior. This research has theoretical and practical implications.